Cellular compatibility of magnetic nanocomposites. (3rd July 2016) - Chen, Jie-Lin; Zhu, Weimin; Guo, Daiqi; Xu, Weili; Chen, Yunfang; Xiong, Jianyi; Lu, Wei; Duan, Li; You, Wei; Wang, Daping; Zeng, Yanjun
Abstract : Objective: To study the cellular compatibility of the magnetic nanocomposite (n-HA/PLLA/Fe2 O3 ) and to discuss the biological behaviors of cells including surface adhesion, proliferation, and expression. The present work provides an experimental basis for medical application. Method: Rat osteoblasts (OB) were co-cultured with the magnetic nanocomposite. Cell proliferation, cell adhesion, and the expression of type I collagen (Col-I) and osteocalcin (OCN) gene were characterized by the cell counting kit-8 (CCK-8) method, scanning electronic microscopy (SEM), and reverse transcription polymerase chain reaction (RT-PCR), respectively. Results: CCK-8 detection showed that there was no difference in cell proliferation on the magnetic nanocomposite between the experimental group and control group ( P > 0.05). SEM indicated that a large amount of cells adhered to the surface and in the pores of the magnetic nanocomposite. As the co-culture time increased, the cells adhering to the magnetic nanocomposite showed an obvious increase. RT-PCR detection showed that as the co-culture time increased, the expression of the Col-I gene was enhanced ( P 0.05). There was no obvious difference in the expression of the OCN gene ( P > 0.05). Conclusion: The magnetic nanocomposite is suitable for cell adhesion, growth, and differentiation with a high cellular compatibility.